Functional role of histone variant Htz1 in the stress response to oleate in Saccharomyces cerevisiae. Issue 4 (7th July 2015) - Liu, Hongde; Li, Guanghui; Liu, Lingjie; Wan, Yakun
Abstract : In response to oleate stress in Saccharomyces cerevisiaes, Histone Two A Z1 (Htz1) undergoes a global redistribution during the glucose-oleate shift. The number of Htz1-bound genes increases, but the number of Htz1-bound ribosome genes decreases with stress. Citrate cycle-associated genes are enhanced and ribosome genes are repressed. Nucleosome dynamics are coupled with Htz1-binding changes upon stress. Multicopy suppressor of SNF1 protein 2 (Msn2) acts an important role in response to the oleate stress. We highlight the dynamics of Htz1 in the oleate stress. Abstract : Chromatin structure is implicated in regulating gene transcription in stress response. Transcription factors, transferases and deacetylases, such as multicopy suppressor of SNF1 protein 2 (Msn2), SET domain-containing protein 1 (Set1) and sucrose NonFermenting protein 1 (Snf1), have been identified as key regulators in stress response. In the present study, we reported the dynamics of nucleosome occupancy, Histone Two A Z1 (Htz1) deposition and histone H3 lysine 4 dimethylation (H3K4me2) and histone H3 lysine 79 trimethylation (H3K79me3) in Saccharomyces cerevisiae under oleate stress. Our results indicated that citrate cycle-associated genes are enhanced and ribosome genes are repressed during the glucose-oleate shift. Importantly, Htz1 acts as a sensor for oleate stress. High-throughput ChIP-chip analysis showed that Htz1 has redistributed across the genome during oleate stress. The number of Htz1-bound genes increases with stress and the number of Htz1-bound ribosome genes decreases with stress. The dynamics of Htz1 and H3K79me3 around transcription factor-binding sites correlate with transcriptional changes. Moreover, we found that nucleosome dynamics are coupled with Htz1 binding changes upon stress. In unstressed conditions (2% glucose), nucleosome occupancy is comparable between Htz1-bound genes and Htz1-depleted genes; in stressed conditions (0.2% oleate for 8 h), the nucleosome occupancy of Htz1-depleted genes is significantly lower than that of Htz1-bound genes. We also found that Msn2 acts an important role in response to the oleate stress and Htz1 is dynamic in Msn2-target genes. Htz1 senses the oleate stress and undergoes a global redistribution and this change couples dynamics of nucleosome occupancy. Our analysis suggests that Htz1 and nucleosome dynamics change in response to oleate stress.